Mechanism of Fires Chemistry and Physical Aspects - Rangwala, Ali S.; Raghavan, Vasudevan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook on fire dynamics provides a comprehensive description of fuels involved in fires, definitions related to fire, thermodynamics for fire calculations, basics of transport processes and fundamental aspects of combustion related to fire, physical descriptions of premixed and non-premixed flames, detailed analysis of the characteristics of fires from solid and liquid fuels, including ignition, spread and burning rates and physical aspects of fire plumes, compartment fires and dust fires. The contents also highlight fundamental aspects related to the evaporation of liquid fuels and pyrolysis of solid fuels which are explained with simplified mathematical expressions. The book includes pedagogical features such as worked examples to illustrate mathematical calculations involved in fire analysis and end-of-chapter review questions. This book proves useful for students, researchers and industry professionals alike.
Chapter 1. Basic Considerations -- Chapter 2. Review of Thermodynamics and Transport Processes for Fires -- Chapter 3. Diffusion and Premixed Flames Related To Fires -- Chapter 4. Burning of Liquids -- Chapter 5. Burning of Solids -- Chapter 6. Properties of Fire Plumes -- Chapter 7. Compartment Fires -- Chapter 8. Dust Flames.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Production engineering; Fire prevention; Buildings$1 (BProtection.s; Engineering Thermodynamics, Heat and Mass Transfer; Thermal Process Engineering; Fire Science, Hazard Control, Building Safety; Thermodynamics; Fires; Thermodynamics; Combustion